Pengalaman Hidup Pasien Stoma Pasca Kolostomi di Rumah Sakit Umum Pusat Dr. Hasan Sadikin Bandung Jawa Barat Tahun 2014 - La Rangki La Rangki; Kusman Ibrahim; Aan Nur’aini (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACTPatient with colostomy followed colorectal has been cancer increasing significantly in Indonesia. Colostomy caused not only physical problems but also psychological and social problems. Health care profesional, especially nurses need to provided hollistic care services to the patients after colostomy. Study with Qualitative method to describe the live experience of the colostomy patient was important. This study was a phenomenological qualitative approach. Data obtained with in-depth interviews to 8 informants consisting of 5 men and 3 women, aged between 30-73 years. The length of time living with a colostomy between 4 months to 6 years. Data were analyzed by using Colaizzi method. Themes emerged from this study: colostomy caused limitations, psychosocial changed, spiritual distres, sexual changed. Living with a stoma required serious attention by health care profesional, access to health services that were important, and decision-making about colostomy influenced by interdisciplinary team and the adequacy of information.Keywords : Lived Experiences, Colostomy, Bandung